Creating Inorganic Chemistry Data Infrastructure for Materials Science Specialists - Kiselyova, Nadezhda N.; Dudarev, Victor A. (Data Analytics and Management in Data Intensive Domains, 2017)
The analysis of the large infrastructure projects of information support of specialists realized in the world in the field of materials science is carried out (MGI, MDF, NoMaD, etc.). The brief summary of the Russian information resources in the field of inorganic chemistry and materials science is given. The project of infrastructure for providing the Russian specialists with data in this area is proposed.